Characterization of NiO-α-MoO3composites synthesized by microwave plasma - Surin Promnopas (2018)
© 2016, Chiang Mai Journal of Science. All Rights Reserved. Pure orthorhombic MoO3and NiO-MoO3composites were successfully synthesized by solid state microwave plasma processing of (NH4)6Mo7O24·4H2O and Ni(NO3)2·6H2O in Ar atmosphere with 3.7 ± 0.1 kPa absolute pressure for 60 min. Phase, morphology, vibration modes and optical properties were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman and Fourier transform infrared (FTIR) spectroscopy, and UV-VIS and photoluminescence (PL) spectroscopy. In this research, formation mechanism of the products was also proposed according to the experimental results.